(untitled) (gjstudies, 2022)
The pursuit of competitive advantage remains the central preoccupation ofstrategic management. Traditionally, cost leadership, as articulated by Porter(1985), has been conceived as a generic strategy achieved through scale, efficiency, and tight control of overhead. However, this static view is increasinglyinadequate in hyper-competitive, digitally-mediated markets where cost structures are fluid and competitive moves are rapidly iterated. This paper arguesfor a fundamental reconceptualization of strategic cost management (SCM). Weposit that SCM is not a defensive, inwardly-focused activity aimed at minimization, but a proactive, strategic capability to shape industry cost norms andcreate asymmetrical competitive positions. Our novel contribution lies in synthesizing frameworks from computational game theory, behavioral economics,and cybersecurity resilience to model SCM as a dynamic, multi-player game ofstrategic interaction.